DAMPAK PENERAPAN TEKNOLOGI INFORMASI DALAM BIDANG E-COMMERCE TERHADAP PENDAPATAN UMKM DI KABUPATEN SUMBAWA - Hapan, Fransiska Maya Kusuma Yanti; Usman, U (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the impact of the implementation of e-commerce information technology on MSMEs income in Sumbawa District. The type of this study was comparative study used to compare the income levels of MSMEs in Sumbawa District before and after the implementation of e-commerce information technology. The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. The type of data used in this study was quantitative data collected from existing sources in the form of annual reports, documents and archives contained in MSMEs in Sumbawa District. Data analysis in this study was carried out using the two-average difference test technique. These testing techniques include the data normality test with Kolmogorov Smirnov test, paired samples statistics test, paired samples correlations test, and paired samples t-test. The results of this study showed that the implementation of e-commerce information technology had a positive impact on the income level of MSMEs in Sumbawa District. The income earned by MSMEs in Sumbawa District had increased after the implementation of e-commerce information technology compared to the income before the implementation of e-commerce information technology. Thus, it can be stated that the implementation of e-commerce information technology is a very important aspect in supporting the increase in MSME income in Sumbawa District.